The artist's journey the travels that inspired the artistic greats - Elborough, Travis (White Lion Publishing, 2023)
"Some truly remarkable works of art have been inspired by artists spending time away from their typical surroundings. From epic road trips and arduous treks into remote territories to cultural tours and sojourns in the finest hotels, this book explores 30 influential journeys taken by artistic greats and reveals the repercussions of those travels on the painters’ personal lives and the broader cultural landscape. Award-winning author Travis Elborough brings each of these trips to life with fascinating insights into the stories behind the creation of some of the world’s most famous paintings, including Henri Matisse’s vivid paintings of Morocco, Katsushika Hokusai’s woodblock prints of Mount Fuji in Japan, Marianne North’s paintings of India and David Hockney’s California pool paintings."--Publisher
Keywords: Artists / Travel; Artists / Biography; Art / History; Artistes / Biographies; Art / Histoire; art history; Travel writing; Récits de voyages